Nitric oxide and its role in exercise physiology - Oral, O. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: Nitric oxide (NO) is quite an essential molecule for human metabolism since it plays an active role in body functions. In the past 20 years, nitric oxide has become a milestone in terms of both athlete physiology and pharmacology studies. The most known and remarkable function of NO is its role in controlling vasodilatation, blood rate, and mitochondrial respiration and thus enhance performance. Therefore, it can be argued that exercise and NO have a positive relationship. EVIDENCE ACQUISITION: In the scientific literature search related to this review, the US National Library of Medicine (PubMed) used MEDLINE and SportDiscus data and the terms "NO," "physical exercise," "vasodilatation," and "performance enhancement." The relevant literature took its source from the research of relevant articles from reference lists derived from data studies. EVIDENCE SYNTHESIS: It was observed that there is a relationship between physical activity and nitric oxide, and it is demonstrated that physical activity enhances NO production. NO is supposed to improve sports performance, promote recovery, and benefit the athlete`s health with its physiological support in vasodilatation, blood flow, and mitochondrial respiration. CONCLUSIONS: Physical activity and nitric oxide resulted to be related. There is a concrete evidence that physical activity enhances NO production. Exercise should be recommended for increasing the level of NO for athletes and for patients with cardiovascular disorders for therapy.